Orff-Schulwerk, Kodály, Dalcroze and Willems in Slovenian Music Schools (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Through our research, we aimed to determine a number of factors relating to the implementation of the Orff-Schulwerk, Kodály, Dalcroze, and Willems approaches and methods in the subject Music Theory in public and private music schools in Slovenia. The factors we investigated are:fprevalence of familiarity with the outlined methods, frequency of implementation, views on perceived effects, and obstacles in incorporating them. The study involved 51 teachers. The research results indicate that teachers are most familiar with the Orff-Schulwerk approach and the Willems method, which they also most frequently integrate into the teaching process. Teachers recognize that these approaches and methods offer the most in terms of holistic development. Teachers identify the obstacles in incorporating these approaches and methods as: insufficient familiarity with each approach, lack of didactic materials, time constraints, classroom size, existing curriculum, and large groups of students.